Combined anaerobic digestion of chicken manure and corn straw: study on methanogenic potential and microbial diversity - Lei Feng; Xiaoyu Lin; Xu Li (Annals of Microbiology, 2022)
Abstract Purpose To explore the methane production potential and microbial community changes of combined anaerobic digestion of chicken manure and corn straw. Increase methane production, reduce the environmental pollution caused by the burning of livestock manure and straw, and provide some theoretical references for the construction and operation of actual biogas projects. Methods Different proportions (3%, 5%, 10%) of corn straw were added to the anaerobic digestion systems of chicken manure in order to improve the C/N ratio and to evaluate the feasibility and potential synergistic effect on the co-digestion. The key point was to use 16S rDNA sequencing to analyze the relationship between the microbial diversity and the hydrolase activity during the anaerobic digestion. Result The results showed that the volumetric gas production of methane in the 3% straw addition group was 227.66 ml/gVS, which was 18% higher than the cumulative methane production in the pure chicken manure experimental group. However, with the increase of straw concentration, methane production and the utilization rate of the raw materials continued to decrease. The change in activity of each hydrolase was in agreement with changes in hydrolytic acidifying bacteria, and the activity of the main hydrolase also increased with the addition of straw; the correlation coefficient was 0.9943. Sequencing results showed that the dominant strains of methanogenic archaea were Methanosarcina, Methanosaeta, Methanobacterium, and Methanospirillum. Mainly for hydrogen-eating, acetic acid-eating methanogens, its role is to use H2, methanol and acetic acid, and other substances to metabolize methane, and convert it into CH4 and CO2. Conclusion The addition of a small amount of straw enhanced the production capacity of hydrogen-nutritive methane to some extent, and the species richness and evenness were also improved, reducing the pollution caused by livestock manure to the environment while controlling the pollution caused by straw burning. Graphical Abstract